1994
DOI: 10.1093/carcin/15.8.1695
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of N-hydroxy heterocyclic amines by human and rat liver microsomes

Abstract: The food-borne carcinogenic and mutagenic heterocyclic aromatic amines undergo bioactivation to the corresponding N-hydroxy (OH)-arylamines and the subsequent N-glucuronidation of these metabolites is regarded as an important detoxification reaction. In this study, the rates of glucuronidation for the N-OH derivatives of 2-amino-3-methylimidazo[4,5-f]-quinoline (IQ), 2-amino-1-methyl-6-phenylimidazo[4,5-b]-pyridine (PhIP), 2-amino-6-methyl-dipyrido[1,2-a:3',2'-d]imidazole (Glu-P-1) and 2-amino-3,8-dimethylimid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 0 publications
3
77
0
Order By: Relevance
“…37,38 Glucuronidation by UGT enzymes is one of the few phase II drug metabolism pathways that significantly contribute to the detoxification of HCAs in liver and extrahepatic tissues. 8,10,11,19,39,40 Large interindividual differences in the rates of PhIP N-oxidation producing the carcinogenic intermediate N-OH-PhIP have previously been observed. 30,41 However, we report here for the first time that its hepatic glucuronidation is also highly variable.…”
Section: Discussionmentioning
confidence: 94%
“…37,38 Glucuronidation by UGT enzymes is one of the few phase II drug metabolism pathways that significantly contribute to the detoxification of HCAs in liver and extrahepatic tissues. 8,10,11,19,39,40 Large interindividual differences in the rates of PhIP N-oxidation producing the carcinogenic intermediate N-OH-PhIP have previously been observed. 30,41 However, we report here for the first time that its hepatic glucuronidation is also highly variable.…”
Section: Discussionmentioning
confidence: 94%
“…Enterohepatic cycling may also exacerbate harm from HCAs that are detoxified through hepatic glucuronidation, including abundant diet-derived compounds such as PhIP, IQ, and MeIQx (56). Studies of the carcinogenic and mutagenic compound IQ have repeatedly observed more DNA adducts and DNA damage in conventional mice versus their germ-free counterparts (57,58).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…[10][11][12]. Results from a human exposure study identified N 2 -OH-PhIP-N 2 -glucuronide as the predominant urinary metabolite (13), suggesting that a large proportion of ingested PhIP is converted into N-OH-PhIP and subsequently conjugated with glucuronic acid by UGTs (14,15). In contrast, the extent of the in vivo role of the glucuronidation pathway for other HCAs, such as 2-amino-3,8-dimethylimidazo [4,5-f]quinoxaline (MeIQx) and 2-amino-3,4,8-trimethylimidazo [4,5-f]quinoxaline (DiMeIQx) remains to be shown but most likely involved UGT1A enzyme family (16).…”
Section: Introductionmentioning
confidence: 99%